Laparoscopy-Assisted versus Open Hepatectomy for Live Liver Donor: Systematic Review and Meta-Analysis. (7th November 2017) - Zhang, Bin; Pan, Yu; Chen, Ke; Maher, Hendi; Chen, Ming-Yu; Zhu, He-Pan; Zhu, Yi-Bin; Dai, Yi; Chen, Jiang; Cai, Xiu-jun
Abstract : Objective . To assess the feasibility, safety, and potential benefits of laparoscopy-assisted living donor hepatectomy (LADH) in comparison with open living donor hepatectomy (ODH) for liver transplantation. Background . LADH is becoming increasingly common for living donor liver transplant around the world. We aim to determine the efficacy of LADH and compare it with ODH. Methods . A systematic search on PubMed, Embase, Cochrane Library, and Web of Science was conducted in May 2017. Results . Nine studies were suitable for this analysis, involving 979 patients. LADH seemed to be associated with increased operation time (WMD = 24.85 min; 95% CI: −3.01 52.78, P = 0.08 ), less intraoperative blood loss (WMD = −59.92 ml; 95% CI: −94.58 −25.27, P = 0.0 007 ), similar hospital stays (WMD = −0.47 d; 95% CI: −1.78 0.83, P = 0.47 ), less postoperative complications (RR = 0.70, 95% CI: 0.51 0.94, P = 0.02 ), less analgesic use (SMD = −0.22; 95% CI: −0.44 −0.11, P = 0.04 ), similar transfusion rates (RR = 0.82; 95% CI: 0.24 3.12, P = 0.82 ), and similar graft weights (WMD = 7.31 g; 95% CI: −23.45 38.07, P = 0.64 ). Conclusion . Our results indicate that LADH is a safe and effective technique and, when compared to ODH.